Akta Notaris Yang Dibuat Dengan Bahasa Asing Tidak Diterjemah Oleh Penerjemah Resmi - Bagaskara, Made Angga; Purwanto, I Wayan Novy (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 02 (2023)DO - 10.24843/AC.2023.v08.i02.p8, 2023)
This research aims to describe regarding the Notary is required to translate the deed he made considering that the Notary is not an official sworn translator and the power of the Notary's deed done in a foreign language but not translated by an official translator. The author's writing method uses normative law due to the absence of norms. Research writing includes using primary legal sources to analyze the Notary Office Act and secondary legal sources using scientific literature. Legislative, conceptual and case approaches. The results of the author's research reveal that the Notary's obligation to translate the deed he made considering that the Notary is not an official sworn translator is indeed a void of norms, even though Article 43 paragraph (2) requires a Notary to translate the deed. Unlike the case with official translators because official translators are people who have been officially sworn in to be able to carry out work in translating deeds, even though a Notary before carrying out his position a Notary must indeed be sworn in but not as an official translator. An authentic deed that is not translated by an official translator who is not sworn in, this causes the deed to be degraded as an authentic deed which has proof as an underhanded deed.